The influence of environmental responsibility disclosure against the financial performance and stock performance: a case study of the environmental insecurity companies listed in Indonesian stock exchange - Elizar Sinambela; Ni Kadek Diwayami Sahasradewi (Proceedings of AICS - Social Sciences, 2017)
The purpose of this research is to analyze the effect of disclosure of environmental responsibility against the financial performance and stock performance. This research is quantitative research with case studies on the 24 companies prone environments listed on the Indonesia stock exchange. The company is a corporate environment prone activity of operations utilizing natural resources and give impact on the environment. Companies that operate in a prone environment tend to reveal the social and environmental information. The data in this study is secondary data obtained from the official website of the Indonesia stock exchange. This research uses the simple regression model with testing two hypotheses. The results showed that the influential environmental responsibility disclosure significantly to financial performance amounted to 30.4%. This condition indicates that environmental responsibility by revealing then can enhance the financial performance of the company. But the disclosure of environmental liability does not have a significant influence on performance shares. This condition indicates that the disclosure of environmental responsibility in this observation does not affect the performance of the stock due to the strong influence of external factors.